Pengembangan Aplikasi E-Learning Berbasis Multimedia (Study Kasus: Penanganan Kerusakan Ringan pada Mobil) - Steve Limin (Peneliti.net, 2022)
These days having private cars for transportation is a necessity for many people and this phenomena is experienced by people in Manado city. Aside from the fact that cars are widely used as means for day-to-day transportations, cars also serve other purposes like to show wealth and status in the society, lifestyle, and more. In spite of all reasons for having a car, this research found that there are only a few of car drivers who have adequate knowledge and skills to identify and take care of any car-related problems. Understanding the spare parts of the car is extremely important to prevent unwanted incidents that may occur as result of trying to fix the car problems without getting any help from the professionals. Another problem is due to the use and availability of appropriate tools when problems happen. Drivers or car owners sometimes do not know how to use the appropriate tools for whatever reasons. Tools are also very expensive and because of this many people prefer to take their cars to the workshops rather than buy tools themselves. Alongside with this, it was also noticed that the manual books are not optimally used by drivers or car owners due to the presentation of information in these books appeared to be very uninteresting and sometimes they are hard to be understood. Car maintenance is another important issue that is often ignored by people that later can cause serious problem to the car. Rapid Application Development (RAD) was opted as the suitable methodological procedure for this project with the help of Unified Modeling Language (UML) tool for object interaction modeling. Activities done in the design stage include designing storyboard, database, object interactions between users and system in the form of UML diagram. In the implementation stage, various features and functions were implemented such as demonstration of fixing car problems, tools selection, workshops and spare parts stores, and more. After that, testing was repeatedly performed to ensure that the application is up and running properly. Also, it was to ascertain that the needs of users and system were met. In conclusion, this application is ready to be used.